Effects of primer-template mismatches on the polymerase chain reaction: human immunodeficiency virus type 1 model studies. - Kwok, S (1990)
We investigated the effects of various primer-template mismatches on DNA amplification of an HIV-1 gag region by the polymerase chain reaction (PCR). Single internal mismatches had no significant effect on PCR product yield while those at the 3'-terminal base had varied effects. A:G, G:A, and C:C mismatches reduced overall PCR product yield about 100-fold, A:A mismatches about 20-fold. All other 3'-terminal mismatches were efficiently amplified, although the G:G mismatches appeared to be more sensitive to sequence context and dNTP concentrations than other mismatches. It should be noted that mismatches of T with either G, C, or T had a minimal effect on PCR product yield. Double mismatches within the last four bases of a primer-template duplex where one of the mismatches is at the 3' terminal nucleotide, in general, reduced PCR product yield dramatically. The presence of a mismatched T at the 3'-terminus, however, allowed significant amplification even when coupled with an adjacent mismatch. Furthermore, even two mismatched Ts at the 3'-terminus allowed efficient amplification.